STRATEGY FOR THE IMPLEMENTING THE PATIENT AND FAMILY CENTERED CARE IN HEALTHCARE SETTING - Buranda, Lucky Sarjono (Jurnal Administrasi Rumah Sakit Indonesia, 2025)
Patient and Family Centered Care (PFCC) is an import part of patient’s autonomy which is the basic human rights of decision-making on what the best they think for their own body. The approach of PFCC is involving not only the patient, but also the family members in providing the decision for their loved one. This article is a narrative literature review with aim to combine several literatures into a strategy for implementing the PFCC in a hospital. An article revealed 7 domains for implementing the PFCC. They are leadership, patient and family engagement, staff engagement, focus on innovations, alignment of staff roles and priorities, organizational structures and processes, and the environment of care. It started with rigorous discussion on the current situation of the organization, the mission and value that aligned with PFCC implementation initiatives. All policies and guidelines must accommodate the FPCC initiatives within the evidence-based medical practice. Piloting the system is the best way to start the implementation of FPCC before it is generally adopt by the entire hospital system. PDSA is one of the best tools to evaluate the pilot. There are two types of PDSA: Model For Improvement – PDSA and FOCUS PDCA. Both essentially offer similar PDSA system, but different in the process and setting.